Model DILEMMA: Pembelajaran Berpikir Kreatif Melalui Penemuan dan Pemetaan Pikiran - Supriyadi Supriyadi; Wulan Ayu Damayanti; Nukhbatul Bidayati Haka (Magister Pendidikan Biologi, Universitas Negeri Medan, 2021)
Creative thinking skills are important competencies for human life. Therefore, these skills need to be prioritized in learning to prepare a generation that is adept at solving problems and able to deal with future uncertainties. This study aims to empower students' creative thinking skills using the Discovery Learning and Mind Mapping (DILEMMA) model. The study used the Quasy Experiment method with The Matching Only Pretest-Posttest Control Group Design. The research instrument was in the form of type B figural essay questions which were developed based on indicators of Paul E. Torrance's creative thinking skills. Data collection techniques using tests (pretest and posttest), and non-test (observation). Data analysis using t-test (Independent sample T-test). The results of data analysis obtained the value of Sig. 0.00 <0.05, means that H1 is accepted. Thus, the DILEMMA model has a significant effect on the creative thinking skills of students. Thus, the results of this study can add to the treasury of studies on improving the quality of learning and have practical benefits for teachers to empower students' creative thinking skills.